Relationship Student Learning Interest To The Learning Outcomes Of Natural Sciences - Harefa, Darmawan; Sarumaha, Murnihati; Telaumbanua, Kaminudin; Telaumbanua, Tatema; Laia, Baziduhu; Hulu, Fatolosa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to determine whether there is a positive and significant relationship and there is an influence between learning interest on Integrated Science learning outcomes. The type of research used in this research is quantitative research with correlational methods. The population in this study were all 65 students of class VII at SMP Negeri 4 Maniamolo. The sampling technique uses a total sampling technique, meaning that the entire population is used as a sample. The instrument in this study used a closed questionnaire and students' science learning outcomes were in the form of odd semester final exam scores. Data analysis techniques were carried out by describing the data, correlational analysis, coefficient of determination and hypothesis testing. The test results in this study indicate that there is a positive and significant relationship between learning interest on science learning outcomes, and there is also an influence between learning interest on Integrated Science learning outcomes. So it was concluded that 1) because students have a sense of pleasure, interest, and a high desire for learning which is seen as giving them benefits and satisfaction, 2) students have a sense of comfort, are aware of the benefits of learning, and know the learning goals that make them interested so that learning occurs. improvement in learning outcomes.